Drum Communication Program Intervention in Older Adults With Cognitive Impairment and Dementia at Nursing Home: Preliminary Evidence From Pilot Randomized Controlled Trial - Miyazaki, Atsuko; Okuyama, Takashi; Mori, Hayato; Sato, Kazuhisa; Ichiki, Masahiko; Nouchi, Rui (Frontiers in Aging Neuroscience, 2020)
Introduction: Inactivity and consequent deterioration of cognitive and physical function is a major concern among older adults with limited walking ability who need a high level of care in nursing homes. We aimed to test whether a drumming communication program (DCP) that uses the rhythmic response function of elderly with dementia and other debilitating disorders improves their cognitive and physical function in a nursing home. Methods: We conducted a randomized controlled trial to investigate the effects of the drumming communication program (DCP) for 46 residents of a nursing home who needed high levels of nursing care. The participants were randomly assigned to an intervention and control group. The intervention group attended 30 minutes of the DCP thrice a week for three months. Cognitive function was measured using the Mini-Mental State Examination (MMSE) and the Frontal Assessment Battery (FAB) at bedside. Physical function was measured using grip strength and active upper limb range of motion with the dominant hand. Body composition was measured using bioelectrical impedance analysis. These measures were performed before and after the DCP intervention period, and data for the two groups were compared following the intervention. Results: The participants had low scores on the MMSE, and 84.78% were using wheelchairs. Following the DCP intervention, the MMSE and FAB scores of the DCP group improved significantly. In terms of motor function, the active range of motion of the wrist palmar and the shoulder flexion improved for the intervention group. Regarding body composition, for the intervention group, the skeletal muscle mass index and total body protein, and the dominant hand muscle mass that was adding physical load decreased. Conclusions: The DCP provided an opportunity to the participants to engage in continued exercise for three months. The intervention group exhibited improved cognitive function and upper limb motion range and changes in body composition. These results suggest that DCP can be used as an intervention method to continuously coordinate exercise to fit various health and cognitive functions.